Air Freight and Logistics Services - Kiso, Fadila; Deljanin, Abidin (Promet - Traffic&Transportation, 2012)
Air transport industry has gradually increased its share of global passenger and freight traffic, and this trend has accelerated in the last 40 years. For the past decade, air-freight traffic growth has outpaced air passenger traffic growth by 1-2% each year. In the past, air-freight sector offered limited services, with heavy reliance on several intermediaries and a significant dependence on air passenger operations. The sector can now be characterized as a sophisticated, innovative one, relying heavily on new electronic technologies, offering a wide range of transport and logistical products through dedicated specialist freight operators. With increasing emphasis on the globalization of trade and economic activity, air-freight growth is expected to continue to outpace air passenger traffic growth. The air-freight growth is expected to be greatest in the Asian markets (intra-Asia; North America-Asia; Europe-Asia and Australasia). The process of physical distribution of freight has become a highly sophisticated operation, with increasingly greater reliance being placed on the use of new technology to assist in the movement, storage, and tracking of consignments. But transport is just one component in this logistics chain. In this paper, air-freight sector is examined in terms of its structure, organization, its role in the supply chains, the main trends in the recent period, constraints facing the sector and the future prospects in air-freight sector. KEY WORDS: air freight organization, development, trends, forecast, logistics services